Effects of Different Types of Exercise Training on the Cortisol Awakening Response in Children - Wegner, Mirko; Koutsandréou, Flora; Müller-Alcazar, Anett; Lautenbach, Franziska; Budde, Henning (Frontiers in Endocrinology, 2019)
Context: Due to great variability of the hypothalamus-pituitary-adrenal (HPA)-axis, research has to produce better-controlled findings to make a more meaningful statement regarding the effect of exercise training (ET) on the cortisol awakening response (CAR), especially in children. Objective: The aim of the study was to investigate the effects of different ET interventions on the CAR in children. Design and setting: We conducted a short-term training study for 10 weeks in primary schools in Westphalia, Germany. Participants: 71 children (9–10 years old) were randomly assigned to a cardiovascular exercise group (n = 27), a motor exercise group (n = 23), or a control group (n = 21). Intervention: An experienced instructor trained the children in an after-school setting in 45 min sessions, three times a week over the course of 10 weeks. Main outcome measure: CAR (0, +30 min) was assessed on 2 schooldays one week apart before and after the 10-week intervention. A Shuttle Run Test was performed to determine the cardiovascular fitness. Motor fitness was assessed using the Heidelberg Gross Motor Test. Results: Children who enhanced their cardiovascular fitness over the course of the intervention showed an increased CAR after the intervention time (B = 0.213), whereas children who underwent a motor exercise intervention and at the same time gained in motor fitness exhibited a decreased CAR after intervention (B = −0.188). Conclusions: It has been speculated that other neurobiological pathways are activated by different exercise interventions. The extent to which these ET effects on CAR can be applied in clinical settings needs further investigation. Précis: The 10-weeks longitudinal effects of cardiovascular vs. motor exercise interventions (three times a week) on CAR in children show that these interventions exert different effects on hypothalamus-pituitary-adrenal (HPA) axis activity.